2008
DOI: 10.1111/j.1365-2648.2008.04844.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of internal marketing and organizational commitment by nurses

Abstract: Hospital managers need to recognize the importance of internal marketing for staff retention and the survival of their organizations as competitive pressure increases. As a great deal of time and costs are involved in educating nurses, the best way to retain outstanding nurses and reduce turnover costs and personnel problems is for employers to understand the needs and expectations of their nursing staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 19 publications
3
87
1
6
Order By: Relevance
“…Hwang and Chi (2005) found that internal marketing has positive impacts on employee job satisfaction and performance of international hotels. Chang and Chang (2007) and Chang and Chang (2009), in their studies carried out with nurses, found positive effects of internal marketing on both job satisfaction and organizational commitment. Tsai and Tang (2008), Başaran et al (2011) found positive relationship between internal marketing practices and service quality in their study.…”
Section: Source: Authorsmentioning
confidence: 99%
“…Hwang and Chi (2005) found that internal marketing has positive impacts on employee job satisfaction and performance of international hotels. Chang and Chang (2007) and Chang and Chang (2009), in their studies carried out with nurses, found positive effects of internal marketing on both job satisfaction and organizational commitment. Tsai and Tang (2008), Başaran et al (2011) found positive relationship between internal marketing practices and service quality in their study.…”
Section: Source: Authorsmentioning
confidence: 99%
“…As shown in this study by Chang and Chang (2009) conducted a study to determine whether a favorable perception of internal marketing is associated with increased organizational commitment. The role of nurses in healthcare treatment is expanding, and becoming more important as time progresses.…”
Section: Internal Marketingmentioning
confidence: 99%
“…According to Hwang and Der-Jang, (2005), internal marketing positively impacts job satisfaction in the context of health services, where customer satisfaction was found higher in organizations within which employees perceived internal marketing to generate high quality services to their clients. In Southern Taiwan, Chang and Chang, (2009) examined two hospitals and found internal marketing positively impact on job satisfaction among nurses.…”
Section: Internal Marketing and Job Satisfactionmentioning
confidence: 99%